Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe CIRC (Cooperative Integrated Reading and Composition) terhadap Kemampuan Pemecahan Masalah Soal Matematika Siswa Kelas VIII SMP Negeri 2 Bengkalis - Muhammad Fahmi (Instructional Development Journal, 2018)
This research aim to to know there is or do not it him difference of ability of trouble-shooting between class using type cooperative model of CIRC (Cooperative Integreted Reading Composition and) at class student of VIII SMP Country 2 Bengkalis District Of Bengkalis Sub-Province of Bengkalis, and difference of[is make-up of ability of trouble-shooting. In research of its problem formula " Do there is difference between class using Model Co-Operative type of CIRC to ability of trouble-shooting of student mathematics in class of VIII SMP Country 2 Bengkalis? and Do there is difference of make-up of between class using type cooperative model of CIRC to ability of trouble-shooting of student mathematics?". This research represent research of experiment kuasi. Population in this research is class student of VIII SMP Country 2 Bengkalis amounting to 114 and people of sampel this research is class of VIII.B amounting to 23 people as experiment class and class of VIII.C amounting to 23 people  as control class.Pursuant to result of analysis can be taken by conclusion that there are difference of ability of trouble-shooting of student mathematics between using type cooperative model of CIRC and conventional study. This seen from complete mean of result learn with type co-operative model of CIRC equal to 83,30 is better the than result learn with conventional study equal to 73,96, and difference of improvement can be seen from test of tes N-Gain t that is equal to 4,07. There by can be concluded that there are influence which are positive when using type cooperative model of CIRC to ability of trouble-shooting of student of SMP Country 2 Bengkalis.